Caracterización física y clasificación taxonómica de algunos suelos dedicados a la actividad agrícola de la provincia de El Oro. - Villaseñor, Diego (2015)
This paper shows the morphological characterization and taxonomic classification of ten representative pedons of farming in El Oro province. The research was conducted in Pajonal (Pj), La Iberia (LI), Santa Inés (SI) place inside Machala cityBuenavista (Bv), Rájaro (Rj), Río Negro (RN), Vega Rivera (VR), Tres Cerritos (TC) place at Pasaje city and Palmales (P1 y P2) place in Arenillas city. For the taxonomic description of the selected soils, the paper has as reference the guidelines of the National Soil Survey Center and the guidelines for Soil Description (FAO, 2009). The physical characterization was performed in the soils laboratory at the Faculty of Agricultural Sciences, Technical University of Machala. As results, two sectors with soils with different taxonomic and morphological properties were identified. Inceptisols y Alfisols, that formed from carbon consolidated sedimentary parent material, and Entisols and Inceptisols unconsolidated sedimentary were generated by frequent deposits of fluvial character. Also, the profiles studied, allowed to characterize the most representative soil conditions in the targeted areas, leading to the continuation of the study, which will be more representative with the increased number of evaluations.